RINGKASAN DISERTASI: PENGGUNAAN BAHASA DALAM KOMUNITAS PERANTAU BUGIS DI PAPUA - Gau, Sukardi (Masyarakat Indonesia, 2012)
This research examines three aspects of language use in the Buginese community in Jayapura, Papua: 1) intra-ethnic and inter-ethnic language choice; 2) language shift among the Buginese youth; and 3) various prominent sociolinguistic issues, such as code alternation and interference. The research ﬁndings show that the language choice among the Buginese typically involves four languages: the Indonesian, the Buginese, the Papuan Malay and the Makassarese Malay. It was found that intra-ethnic language showed patterns of code alternation and interference involving all the above languages. The Buginese only use the Indonesian and the Papuan Malay languages when interacting with other ethnic groups. Furthermore, this research found that language shift occurs, particularly among the younger Buginese generation. Generally, the Buginese children who have been born and raised in Papua do not speak the Buginese language and even have shifted to the Indonesian and the Papuan Malay languages while interacting with other Buginese. The Buginese language in general is spoken by the older generation and those who spoke the Buginese before migrating to Papua. This research has contributed new knowledge in the Buginese studies, particularly regarding those of the Buginese who have migrated to other Nusantara regions.